OPTIMASI AIR IRIGASI PADA SUB PESANGGARAN KABUPATEN BANYUWANGI MENGGUNAKAN WEAP (WATER EVALUATION AND PLANNING) - Pratita Dewi; Wiwik Yunarni; Gusfan Halik (Jurnal Teknik Sipil, 2020)
Water requirement in Pesanggaran is rice fields, while the availability of irrigation water is obtained from rainfall and irrigation discharge. The water balance is calculated by using a tool such as the Water Evaluation and Planning (WEAP) where the results of the WEAP are in the form of a broad percentage of water coverage that can be covered (Coverage). The results of the WEAP calculation are in the form of Coverage as a reference in calculating profits for each year. Optimization in the Very Dry and Normal Year is the existing of where the start of planting begins in December period 1 while the optimize has the start of planting in the December period 3 in the Dry and Wet Season. WEAP optimization is seen in the number of Coverage values where the coverage value for a Dry Year before optimization is 99.34%, and after optimization is 100%, Wet Year before optimization is 99.1%, and after optimization is 100%, for Very Dry Year Coverage value is 95.69%, and Normal Year Coverage as 99.16%.